Character Education Value from Ten Folktales in Indonesia as Cyber Literature - Imam Santosa; Lutfi Lutfi; Kheryadi Kheryadi; Yulian Dinihari; Wuriy Handayani; Sufi Alawiyah (Laboratorium Bantenologi UIN Sultan Maulana Hasanuddin Banten, 2022)
In the development of technology, all aspects experience the same development, including literature. Technology had greatly influenced the production and reception of literature. Changes in literary works by utilizing current technological media can also be called cyber literature. However, the ease of technology might lead problems. The teacher who would use cyber literature as learning material took it without any guideline on what is the value that existed in the cyberliterature. So that this study aimed to analyze character education that appears in folklore cyber literature in Indonesia. The results of this study will be a guide for high school English teachers in choosing what characters to use in narrative learning using folklore. The approach used in this research was a descriptive qualitative approach. The data source of this research was cyber literature in the form of folklore. The selection of the title of folklore in Indonesia was based on the results of a poll from the SINDO newspaper which found that there were 10 popular folk tales. The result of the study showed that from 10 the most popular folklore in the internet, 6 out of 18 characters existed in the story. They were Responsible, hard work, honesty, self-reliance, creative, and love country. Even though, the value mostly based on the protagonist of the story, we could also see the contra value that promoted by the antagonist, such as dishonesty..